Impact of Cluster Formation on Innovation in the Health Subsector in Colombia - Edwin Leonardo Mendez Ortiz; Alejandra Pulido-López; Jose Armando Hernandez Bernal; Jorge Hernan Cifuentes Valenzuela (SAGE Open)
This article aims to evaluate the impact of cluster characteristics, including cooperation and information sources, on the innovative performance of companies in the health sector in Colombia. It analyzes how collaboration and knowledge exchange within clusters affect innovation outcomes and provides information on their role as mechanisms to foster competitiveness and enhance innovation in the health sector. An ordered multinomial logit model was used, where the dependent variable was the innovative performance of companies in the health sector, classified into four categories: intention to innovate, initiation and abandonment of the innovation process, and innovation for the national and international market. Explanatory variables included aspects of cooperation and sources of information. The Survey of Development and Technological Innovation EDIT VI, conducted by the National Administrative Department of Statistics of Colombia, was used to collect data from 408 companies in the health sector in Colombia during the period 2016 to 2017. The research findings suggest a positive relationship between cluster formation and companies’ innovative performance in Colombia’s health sector, observed in business cooperation and sources of information. In addition, these characteristics of the cluster promote innovation at different levels, from the initial intention to the achievement of innovations for national and international markets. This article contributes to the literature by generating knowledge about the role of dual causality variables as mediators between effort and innovative success in health service companies. It will also have managerial and social implications, serving as an input for strategic decision-making and the design of public policies promoting sustainable innovation.